BRAND AWARENESS DESA WISATA MELALUI KONTEN MEDIA SOSIAL - Deva Nita Mulya; Yashinta Putri Dwi Astuti; Ignatius Bias Galih Prasadhya; Ricky Arnold Nggili (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
This Community Service Program was conducted in Kradon Lor Tourism Village, which has the potential for camping-based tourism but has not been optimally supported by the utilization of social media. The main problems faced by the partner included limited human resource capacity in managing digital content and the absence of a measurable and relevant social media–based promotional strategy. The objective of this program was to enhance the understanding and capacity of village officials, the Village-Owned Enterprise (BUMDes), and the Youth Organization (Karang Taruna) in utilizing social media as a tool to strengthen tourism village brand awareness. The program was implemented through four stages: planning (observation and problem identification), implementation (socialization and capacity building on social media content), evaluation, and reporting. The results indicate an improvement in participants’ understanding of the role of social media in promoting tourism villages, as evidenced by enhanced participant comprehension based on post-activity interviews and the establishment of a shared commitment to managing the tourism village’s social media accounts. In addition, participants were able to identify relevant and sustainable promotional content. This program proved effective as an initial step toward strengthening digitally based tourism village development. Further recommendations include technical assistance in content creation, consistent social media implementation, and evaluation of its impact on increasing tourist visits.